Apuntes para una historia de la Ley del contrato de seguro del Perú - Meza Carbajal, Luis Alberto (Revista de Derecho, 2019)
This study refers to the historical process that gave rise to the Peruvian InsuranceContracts Act 2012 (ica). It aims to identify the proposals and performance of thestakeholders that preceded this important piece of legislation. To that end, documentsfrom the Peruvian Congress and other sources are mainly used. Among itsconclusions, it states that unlike previous proposals the focus of the project thatgave rise to the ica, that is, the sbs Project 2005, was the need to protect the insuredparty and promote legal balance in insurance relationships, based on the StiglitzProject and contributions from local experts and organizations. It also identifiesthe participation of stakeholders, their positions and proposals. Finally, the studyrecommends that Draft Law 4635/2014-cr, which seeks the exclusion of the socalled“gross risks” from the scope of the ica 2012, should not be approved by thePeruvian Congress.
Keywords: Insurance Contract; Insurance Contract Act 2012; History of the Insurance Contract Act; History of the Insurance Contract Actgross risks; gross risks; Peru.